(untitled) (Research, Society and Development, 2022)
Dengue is a public health problem, being an acute febrile disease, of viral etiology and that manifests itself in different ways, from asymptomatic to severe and hemorrhagic conditions. The present study aimed to evidence the determining factors for the prevalence of dengue in the notification microregion of Altamira in the period between 2014 and 2020. For this, a descriptive, analytical, retrospective and quantitative epidemiological study was used as a methodology, in which data were collected through the TABNET application of the Department of Informatics of the Unified Health System (DATASUS) of the IBGE micro-region, referent Altamira-Pará. After collection, this study showed that rainfall rates are positively correlated with the incidence of dengue in the analyzed region and predict 61.83% of data variability. In addition, outbreaks were observed in some municipalities in the study site. The most affected populations were women, mixed race, between 20 and 39 years old, with incomplete schooling between the 5th and 8th grade of elementary school. As for the natural history of the disease, the clinical-epidemiological assessment was the most frequently performed diagnostic criterion, with evolution to cure occurring in 67.89% of notifications. Based on these data, it will be possible to plan dengue epidemic prevention strategies, knowing in advance the incidence of rain.